Faktor Risiko COVID-19 pada Anak - Debora K. Pangow; Novie H. Rampengan; Rocky Wilar (e-CliniC, 2023)
Abstract: The prevalence of COVID-19 cases is still increasing in children, as well as the morbidity and mortality rates. Therefore, it is necessary to understand the risk factors involved in the incidence of COVID-19 infection in children. This study aimed to identify and analyze the risk factors for the transmission of COVID-19 in children. This was a literature review study using four databases namely Scopus, ProQuest, Pubmed, and Science Direct. The results obtained 16 literatures about the risk factors for COVID-19 in children with the basic concept of the epidemiological triad of COVID-19 risk factors, namely the host, agent, and environment. The literatures indicated that the host risk factors were gender, vitamin D deficiency, age, asthma comorbid or underlying medical conditions, and race. The agent risk factors were the emergence of the delta virus variant, meanwhile the environmental risk factors were the exposure to viruses in the household or family cluster, exposure to endemic areas, exposure to bus travel, virus transmission at school, and close contact with people diagnosed with COVID-19. In conclusion, risk factors for COVID-19 in children with interaction of transmission factors of COVID-19 which are host, agent, and environment cause the rapid development of new coronavirus cases. Most transmission of COVID-19 in children is derived from family contact (environment). Keywords: risk factors for COVID -19; transmission in children Abstrak: Prevalensi kasus COVID-19 terus meningkat pada anak, demikian pula angka kesakitan maupun angka kematian. Oleh karena itu faktor risiko yang terlibat kejadian infeksi COVID-19 pada anak perlu dipahami secara detil. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis faktor risiko penularan COVID-19 pada anak. Jenis penelitian ialah suatu literature review yang menggunakan empat pengkajian database yaitu Scopus, ProQuest, Pubmed, dan ScienceDirect. Hasil penelitian mendapatkan 16 literatur yang meneliti faktor risiko COVID-19 pada anak, dengan konsep dasar trias epidemiologi faktor risiko COVID-19 yaitu pejamu, agen, dan lingkungan. Faktor-faktor risiko pejamu yaitu jenis kelamin, defisiensi vitamin D, usia, dan komorbiditas asma atau kondisi medis yang mendasari, dan ras. Faktor risiko agen yaitu muncul-nya varian virus delta, sedangkan faktor lingkungan yaitu paparan virus dalam rumah tangga atau klaster keluarga, paparan daerah endemik, paparan perjalanan bus, penularan virus disekolah dan kontak dekat dengan orang terdiagnosis COVID-19. Simpulan penelitian ini ialah faktor-faktor risiko kejadian infeksi COVID-19 pada anak dengan interaksi faktor penularan COVID-19 yaitu faktor pejamu, agen dan lingkungan, mengakibatkan perkembangan kasus coronavirus baru yang sangat cepat. Penularan pada anak terbanyak berasal dari riwayat kontak keluarga (lingkungan). Kata kunci: faktor risiko COVID-19; penularan pada anak